Contribution à l’étude de quelques traits de vie de l’oursin Paracentrotus lividus (Lamarck ,1816) au niveau de la cote de Mostaganem ( - KHELAFI, FATIMA ZOHRA; SENOUCI, ZOUBIR (My University, 2019)
In the ecological field, there are many studies on the use of bioindicators to determine the quality of seawater. In our study, we chose the indicator of benthic zone, the echinacea sea urchin, Paracentrotus lividus (Lamarck, 1816), to determine the trophic activity of the Salamander biotope in the Mostaganem littoral. The thesis takes three months in February and up to April from station sampling, with the analyst's result being present on average and in standard deviation. Our result takes two axes: classification of the first axis with physiological parameter (IRm index repletion, IGm index gonad) and relation between biometric parameter, the means of variation of the IRm index makes it possible to detect the relationship between the trophic contributions and the growth of the individual, according to our study, month-by-month fluctuations in the IGm index indicate the spawning period for the bioindicator species that, according to our results, was expected to be in the peak of the spring season. The second axis is the analysis of the digestive content by the contact method of JONES (1968). This method revealed that the livid sea urchin had a selective feeding behavior, with a preference for brown algae.
Keywords: Paracentrotus lividus; Salamander; physiologies index; IGm; IRm; Jones (1968); digestive contents; Brown algae